2020
DOI: 10.1136/gutjnl-2020-321309
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of antiviral treatment in adult patients with immune-tolerant phase chronic hepatitis B

Abstract: ObjectiveThe cost-effectiveness of antiviral treatment in adult immune-tolerant (IT) phase chronic hepatitis B (CHB) patients is uncertain.DesignWe designed a Markov model to compare expected costs and quality-adjusted life-years (QALYs) of starting antiviral treatment at IT-phase (‘treat-IT’) vs delaying the therapy until active hepatitis phase (‘untreat-IT’) in CHB patients over a 20-year horizon. A cohort of 10 000 non-cirrhotic 35-year-old patients in IT-phase CHB (hepatitis B e antigen-positive, mean seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Our recent cost‐effectiveness analysis indicated that earlier treatment initiation with normal ALT levels and high viral load may be cost‐effective compared with deferring the treatment until the appearance of active hepatitis phase in adult patients with CHB, 70 considering highly potent long‐term efficacy and safety of current anti‐HBV drugs that have high genetic barrier to resistance and decreasing cost 71–73 . In accordance, overall medication adherence rate in CHB patients has been consistently reported to be high (>90%) by many previous studies 74–76 …”
Section: Resultsmentioning
confidence: 99%
“…Our recent cost‐effectiveness analysis indicated that earlier treatment initiation with normal ALT levels and high viral load may be cost‐effective compared with deferring the treatment until the appearance of active hepatitis phase in adult patients with CHB, 70 considering highly potent long‐term efficacy and safety of current anti‐HBV drugs that have high genetic barrier to resistance and decreasing cost 71–73 . In accordance, overall medication adherence rate in CHB patients has been consistently reported to be high (>90%) by many previous studies 74–76 …”
Section: Resultsmentioning
confidence: 99%
“… 26 Similarly, compared with delaying treatment until progression to active hepatitis phase in CHB patients, starting antiviral therapy in the immune-tolerant phase is more cost-effective, decreasing drug costs and affecting productivity loss. 27 With decreasing cost of nucleos(t)ide analog in the forthcoming years, the cost-effectiveness of treatment could be further improved. TAF was listed in China’s medical insurance reimbursement catalog (patients paid about 647-3,234 RMB per year) in December 2019, so it is reasonable to believe that TAF, a cost-effective regimen of antiviral therapy, is currently available.…”
Section: Discussionmentioning
confidence: 99%
“…If the individual does not infect others with HBV, the “resistance” cannot spread. Even if therapy is given lifelong, it is cost‐effective in Asian countries because it offsets the direct health care costs of managing late complications, such as decompensation, HCC, admissions, and transplantation, and the indirect costs of low economic productivity and wage losses because of CHB 18 …”
Section: Challenges On the Road To Eliminationmentioning
confidence: 99%